(untitled) (قضايا سياسية, 2025)
The Russian-Ukrainian war marked a new and unprecedented turning point in Europe, particularly in the history of the European continent, especially since the end of World War II. This war led to the emergence of international and regional interactions, particularly through the division of the conflicting parties between Russia, on the one hand, and Ukraine and its allies, primarily the United States, as well as Western European countries. As a result, the war witnessed a significant and continuous escalation, contributing to the draining of vast sums of money in the form of financial, military, and other support for Ukraine, particularly from its allies in Europe. It led to widespread repercussions, particularly its negative impact on the European economy, which has become evident in European countries, particularly in terms of energy prices and their fluctuations, food insecurity, and the waves of refugees to Europe and their living costs.